Gastronomy as an intangible element in the declaration of assets of cultural interest in the Valencian Community (Spain) and its influence on the tourist destination - Ramón Fernández, Francisca (2020)
In this paper we analyze the importance of gastronomy, mentioned in the Declaration of Assets of Cultural Interest of the Valencian Community, Spain; which refers to this cultural manifestation that has a territorial and cultural identity value, and that becomes a relevant element to choose a tourist destination. The gastronomic tourist, like the city tourist, shows interest in tasting typical dishes of a destination. Gastronomic tourism is an activity that represents an increase in resources in the tourist area, and consequently, contributes to the preservation of cultural identity.